Migration in times of uncertainty: on the role of economic prospects - Czaika, M (International Migration Institute, 2012)
Uncertainty and risk perceptions are important elements in the decision-making process about migration. This study outlines a ‘migration prospect theory’, i.e. an application and advancement of Kahneman and Tversky’s (1979; Tversky and Kahneman 1991) original prospect theory, which aims to explain short-term fluctuations of migration flows as a consequence of expectation-based adjustment about future economic prospects. I argue that individuals with migration intentions continuously assess general economic prospects, including the labour market situation, at home and abroad in order to form reference points and updates for their migration-related expectations. Consequently, deviations from reference points generate (short-term) expectation-based utility gains or losses for potential migrants, which affect the value of the migration option. This can lead to a cancellation or procrastination of the individual migration project. Based on an analysis of annual and quarterly intra-European migration inflows to Germany between 2001 and 2010, supportive empirical evidence about some key implications of this migration prospect theory is found: first, migration flows respond more strongly to negative than to equal-sized positive economic prospects, indicating loss aversion of potential migrants; second, expectation-based prospects about the future economic situation in the home and in the potential destination country can counterbalance or enforce structural economic incentives based on real economic aggregates; and third, migration flows show a diminishing sensitivity for larger fluctuations in expectation-based adjustments of economic prospects.